Answer:
The expression that is greater is a (b - c)
Step-by-step explanation:
- a < 0 and c > b, this means <u>(by the addition property)</u> that c - c > b - c⇒0 > b - c
so for the product <u>a(b - c) </u>we would have a multiplication of a negative number <em>a</em> and another negative number <em>(b - c)</em>. We know that the result of the <u>multiplication of two negative numbers is a positive number.</u>
Therefore, a (b - c) > 0
- a < 0 and c > b, this means <u>by the addition property</u> that c - b > b - b⇒ c - b > 0
so for <u>a(c - b)</u>, we have the negative number <em>a</em> multiplied by the positive number <em>(c - b). </em>We know that the result of the <u>multiplication of a negative number by a positive number is negative. </u>
<u>Therefore a (c - b) < 0</u>
Thus, the expression that is greater is the positive one which is a (b - c)
Answer:
0.03734439834
Step-by-step explanation:
Sort the numbers in ascending or descending order, then eliminate the greatest and least numbers until you're left with the middle two. The median is the average of the last two numbers.
For example, the median for the set
![\{2,10,-1,4\}=\{-1,2,4,10\}](https://tex.z-dn.net/?f=%5C%7B2%2C10%2C-1%2C4%5C%7D%3D%5C%7B-1%2C2%2C4%2C10%5C%7D)
is 3 because the middle two numbers are 2 and 4, and their average is
![\dfrac{2+4}2=3](https://tex.z-dn.net/?f=%5Cdfrac%7B2%2B4%7D2%3D3)
.
Answer:
Compound interest = Rs 1,575 (Approx.)
Step-by-step explanation:
Given:
Amount invested = R.s 6,500
Rate of interest = 7.5% per annum
Number of year = 3 year
Find:
Amount of compound interest
Computation:
Compound interest = P[(1+r)ⁿ - 1]
Compound interest = 6500[(1+7.5%)³ - 1]
Compound interest = 6500[(1+0.075)³ - 1]
Compound interest = 6500[(1.075)³ - 1]
Compound interest = 6500[1.2423 - 1]
Compound interest = 6500[0.2423]
Compound interest = 1574.95
Compound interest = Rs 1,575 (Approx.)